Enteric nervous system damage caused by abnormal intestinal butyrate metabolism may lead to functional constipation - Wang, Le; Lv, Wan-Qiang; Yang, Jun-Ting; Lin, Xu; Liu, Hui-Min; Tan, Hang-Jing; Quan, Ru-Ping; Long, Pan-Pan; Shen, Hui; Shen, Jie; Deng, Hong-Wen; Xiao, Hong-Mei (Frontiers in Microbiology, 2023)
Functional constipation (FC) is a high morbidity gastrointestinal disease, for which dysfunction in enteric nervous system is a major pathogenesis mechanism. To enhance our understanding of the involvement of intestinal microbiota and its metabolites in the pathogenesis of FC, we conducted a shotgun metagenomic sequencing analysis of gut microbiota and serum short-chain fatty acids (SCFAs) analysis in 460 Chinese women with different defecation frequencies. We found the abundance of Fusobacterium_varium, a butyric acid producing bacterium, was positively correlated (p=0.0096) with the frequency of defecation, but the concentrations of serum butyric acid was negatively correlated (p=3.51E-05) with defecation frequency. These results were verified in an independent cohort (6 FC patients and 6 controls). To further study the effects of butyric acid on intestinal nerve cells, we treated mouse intestinal neurons in vitro with various concentrations of butyrate (0.1mM, 0.5mM, 1mM, 2.5mM). We found that intestinal neurons treated with 0.5 mM butyrate proliferated better than the other treatment groups, along with significant differences in cell cycle and oxidative phosphorylation signal pathways. We conclude that the decrease of butyrate production resulted from the reduced abundance of Fusobacterium in gut microbiota will affect the proliferation of intestinal neurons and the energy supply of intestinal cells. However, with the advancing of FC disease, the consumption and excretion of butyric acid will be reduced, leading to its accumulation in the intestine. The accumulation of excessive high amount of butyric acid will also inhibit the proliferation of nerve cells, and subsequently exacerbate the disease.